The combinatorics of LCD codes: linear programming bound and orthogonal matrices. (2017) - Dougherty, Steven T.; Kim, Jon-Lark; Ozkaya, Buket; Sok, Lin; Solé, Patrick
Linear complementary dual (LCD) codes are binary linear codes that meet their dual trivially. We construct LCD codes using orthogonal matrices, self-dual codes, combinatorial designs and Gray map from codes over the family of rings Rk . We give a linear programming bound on the largest size of an LCD code of given length and minimum distance. We make a table of lower bounds for this combinatorial function for modest values of the parameters.